A novel approach to completely alleviate peripheral neuropathic pain in human patients: insights from preclinical data - Shehab, Safa; Hamad, Mohammad I. K.; Emerald, Bright Starling (Frontiers in Neuroanatomy, 2025)
Neuropathic pain is a pervasive health concern worldwide, posing significant challenges to both clinicians and neuroscientists. While acute pain serves as a warning signal for potential tissue damage, neuropathic pain represents a chronic pathological condition resulting from injury or disease affecting sensory pathways of the nervous system. Neuropathic pain is characterized by long-lasting ipsilateral hyperalgesia (increased sensitivity to pain), allodynia (pain sensation in response to stimuli that are not normally painful), and spontaneous unprovoked pain. Current treatments for neuropathic pain are generally inadequate, and prevention remains elusive. In this review, we provide an overview of current treatments, their limitations, and a discussion on the potential of capsaicin and its analog, resiniferatoxin (RTX), for complete alleviation of nerve injury-induced neuropathic pain. In an animal model of neuropathic pain where the fifth lumbar (L5) spinal nerve is unilaterally ligated and cut, resulting in ipsilateral hyperalgesia, allodynia, and spontaneous pain akin to human neuropathic pain. The application of capsaicin or RTX to the adjacent uninjured L3 and L4 nerves completely alleviated and prevented mechanical and thermal hyperalgesia following the L5 nerve injury. The effects of this treatment were specific to unmyelinated fibers (responsible for pain sensation), while thick myelinated nerve fibers (responsible for touch and mechanoreceptor sensations) remained intact. Here, we propose to translate these promising preclinical results into effective therapeutic interventions in humans by direct application of capsaicin or RTX to adjacent uninjured nerves in patients who suffer from neuropathic pain due to peripheral nerve injury, following surgical interventions, diabetic neuropathy, trauma, vertebral disc herniation, nerve entrapment, ischemia, postherpetic lesion, and spinal cord injury.